Intestinal Inflammation Modulates the Epithelial Response to Butyrate in Patients With Inflammatory Bowel Disease - Ferrer-Picón, Elena (Inflamm Bowel Dis, 2020)
BACKGROUND: Butyrate-producing gut bacteria are reduced in patients with active inflammatory bowel disease (IBD), supporting the hypothesis that butyrate supplementation may be beneficial in this setting. Nonetheless, earlier studies suggest that the oxidation of butyrate in IBD patients is altered. We propose that inflammation may decrease epithelial butyrate consumption. METHODS: Non-IBD controls and IBD patients were recruited for the study. Stool samples were used for short-chain fatty acid and bacterial butyryl CoA:acetate CoA-transferase quantification. Colonic biopsies and ex vivo differentiated epithelial organoids (d-EpOCs) treated with butyrate and/or tumor necrosis factor alpha (TNFα) were used for analyzing the expression of transporters MCT1 and ABCG2, metabolic enzyme ACADS, and butyrate receptor GPR43, and for butyrate metabolism and consumption assays. RESULTS: We observed that lower stool content of butyrate-producing bacteria in active IBD patients did not correlate with decreased butyrate concentrations. Indeed, the intestinal epithelial expression of MCT1, ABCG2, ACADS, and GPR43 was altered in active IBD patients. Nonetheless, d-EpOCs derived from IBD patients showed SLC16A1 (gene encoding for MCT1 protein), ABCG2, ACADS, and GPR43 expression levels comparable to controls. Moreover, IBD- and non-IBD-derived d-EpOCs responded similarly to butyrate, as assessed by transcriptional regulation. TNFα significantly altered SLC16A1, ABCG2, and GPR43 transcription in d-EpOCs, mimicking the expression profile observed in biopsies from active IBD patients and resulting in reduced butyrate consumption. CONCLUSIONS: We provide evidence that the response to butyrate is not intrinsically altered in IBD patients. However, TNFα renders the epithelium less responsive to this metabolite, defeating the purpose of butyrate supplementation during active inflammation.